2-(4-Morpholinecarbothioylsulfanyl)acetic acid - Kong Mun Lo; Seik Weng Ng (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title compound, C7H11NO3S2, contains two independent molecules with similar molecular structures. The morpholine ring adopts a chair conformation, and the C2N—C(=S)—S fragment is planar in the two independent molecules (r.m.s. deviations = 0.01 and 0.02 Å). The two molecules are disposed about a false center of inversion and are held together by a pair of O—H...O hydrogen bonds. The crystal studied was a racemic twin; the minor twin component refined to 17%.